Exploring the Links Between Forest Stewardship Council Certification and Biodiversity Outcomes at a Global Level - Parag Kadam; Puneet Dwivedi (Land)
Forests contain just under 58% of all known species globally, with approximately 61% of these found in countries with Forest Stewardship Council (FSC)-certified forests. Few studies have directly analyzed the association between biodiversity and certification, often focusing on limited geographical or temporal scopes. There is a lack of understanding regarding the socio-political and ecological drivers of FSC certification’s relationship with biodiversity conservation. We assess the associations between country-level characteristics and the relationship between FSC’s forest management (FSC-FM) certification area and independently made biodiversity estimates from the International Union for Conservation of Nature (IUCN). Specifically, using generalized random forests (GRF) and data from 91 countries between 2008 and 2019, we examine the associated factors that govern FSC-FM certifications relationship with percentage threatened species. The results indicate that increasing FSC-FM-certified areas is linked to a reduction in the percentage of threatened species by 0.1 to 0.15. Moreover, FSC-FM certifications show a positive relationship with biodiversity in regions with high population densities and significant tree cover loss. Enhanced perception of corruption control and reduced extraction of non-forestry resources further strengthen this association. These findings provide the FSC with strategic insights to expand FM certification, contributing to biodiversity conservation through sustainable forest management.